Integrating conductive electrodes into hydrogel-based microfluidic chips for real-time monitoring of cell response - Pourmostafa, Ayda; Bhusal, Anant; Haridas Menon, Niranjan; Li, Zhenglong; Basuray, Sagnik; Miri, Amir K. (Frontiers in Bioengineering and Biotechnology, 2024)
The conventional real-time screening in organs-on-chips is limited to optical tracking of pretagged cells and biological agents. This work introduces an efficient biofabrication protocol to integrate tunable conductive hydrogel electrodes into organs-on-chips. We established our method of fabricating cell-laden hydrogel-based microfluidic chips through digital light processing-based 3D bioprinting. Our conductive ink includes poly-(3,4-ethylene-dioxythiophene)-polystyrene sulfonate (PEDOT: PSS) microparticles doped in poly-ethylene glycol diacrylate (PEGDA). We optimized the manufacturing process and characterized our conductive ink for different 3D bioprinting parameters, geometries, and materials conditions. While the literature is limited to 0.5% w/v for PEDOT: PSS microparticle concentration, we increased their concentration to 5% w/v with superior biological responses. We measured the conductivity in the 3-15 mS/m for a range of 0.5-5% w/v microparticles, and we showed the effectiveness of 3D-printed electrodes for predicting cell responses when encapsulated in gelatinmethacryloyl (GelMA). A higher cellular activity was observed in the case of 5% w/v microparticles compared to 0.5% w/v microparticles. Electrochemical impedance spectroscopy measurements indicated significant differences in cell densities and spheroid sizes embedded in GelMA microtissues. Our protocol makes a benchmark for real-time monitoring of cell responses.